Experimental FTIR characterization of kidney stones, DFT analysis of CaC2O4 and its interactions with lysozyme (BIBECHANA, 2024)
Kidney stone is an alarming global disease due to its rising incidence and prevalence. FTIR spectroscopic analysis reveals that calcium oxalate is one of the most frequent chemical constituents in kidney stones. DFT calculations indicate that the calcium oxalate can interact through charge transfer process in biological activities. Among various proteins, lysozyme is one of the promoter proteins in nephrolithiasis of calcium oxalate type kidney stone. The location, conformation and interactions of calcium oxalate with the active residues of lysozyme contribute the binding energy of -4.18 kcal/mol. The characterization of kidney stones, DFT calculations of calcium oxalate, and binding interactions of calcium oxalate-lysozyme complex contribute to the understanding of nephrolithiasis.